Representation of the Chepang in Local Government: A Study of Local Election 2022 - Adhikari, Rishiram (International Research Journal of MMC, 2022)
The study analyzes the representation of the Chepang in the local election 2022. Political representation is only the way to participate people into decision making process. The issue of proper representation has been raised in since long time. Constitutionally and legally Nepal has made some provisions of proper representation and implemented through election process. In this context, the study concentrates on how is the situation of representation of the Chepang in local government that has just been formed by the election of April 2022. The study was followed qualitative research design and data were collected through secondary sources. In qualitative research design, the study applied interpretative technique and data were interpreted projected through table. Conclusion has been made on the basis of data interpretation and analysis. Through data it is found that the situation of the political representation of the Chepang in local government is in increasing trend but the current elected number is not sufficient decision making process.